Monte-Carlo simulations of the two-dimensional NMR T2-T2 exchange of fluids in porous media - Moldovan, Daniel; Fechete, Radu; Demco, Dan Eugen; Culea, Eugen; Blümich, Bernhard (Diffusion Fundamentals, 2009)
The effects of molecular exchange processes on the two-dimensional (2D) NMR T2-T2 distributions obtained by Laplace inversion were studied by numerical simulations. The Monte–Carlo technique is used to generate free random walks of a large number of molecules within space regions characterized by different relaxation times. Molecular exchange processes are considered during CPMG encoding periods as well as during the storage period, τstore. Systematic simulations were performed as function of NMR parameters like the storage period, τstore and geometric or physical system properties.